PENGARUH TINGKAT PENDAPATAN DAN PEMAHAMAN HAJI DAN UMRAH TERHADAP MINAT CALON JAMAAH DALAM MENDAFTAR HAJI DAN UMRAH DI KBIH WILAYAH KABUPATEN TASIKMALAYA - M. Hilman Abdul Halim; Hasan Basri; Mei Amimah (ARMUZNA : Jurnal Manajemen Haji dan Umrah (MHU), 2024)
This research aims to determine 1. The influence of the income level of prospective pilgrims on their interest in registering for Hajj and Umrah at the Tasikmalaya Regency KBIHU. Interested in registering for Hajj and Umrah at Tasikmalaya Regency Travel or Guidance (KBIHU). For this research method, the samples taken were 100 prospective pilgrims at the KBIHU Tasikmalaya Regency. The sampling technique used was purposive sampling. This research uses a quantitative approach and multiple linear regression analysis methods. The data source used is primary data by distributing questionnaires. The results of this research are 1. There is no influence of the income level of prospective pilgrims on interest in registering for Hajj and Umrah at KBIHU Tasikmalaya Regency with Sig = 0.000 < 0.05 and tcount > ttable, namely, 1,314 > 0.192 2. There is an influence of the level of understanding of prospective pilgrims on interest. Registering for Hajj and Umrah at KBIHU Tasikmalaya Regency Sig = 0.000 < 0.05 and tcount > ttable, namely, 6.679 > 0.609 3. There is an Influence of Income Level and Understanding of Prospective Pilgrims on Interest in Registering for Hajj and Umrah at Travel or Guidance (KBIHU) Tasikmalaya Regency Sig = 0.000 < 0.05 and Fcount is greater than Ftable, namely 37.688 > 2.70. The conclusions of this research based on the results obtained are 1. There is no influence of the income level of prospective pilgrims on interest in registering for Hajj and Umrah at KBIHU Tasikmalaya Regency 2. There is an influence of the level of understanding of prospective pilgrims on interest in registering for Hajj and Umrah at KBIHU Tasikmalaya Regency 3. The influence of income level and Prospective pilgrims' understanding of their interest in registering for Hajj and Umrah at Tasikmalaya Regency Travel or Guidance (KBIHU).